Resistance Mechanisms to Anti–Epidermal Growth Factor Receptor Therapy in RAS/RAF Wild-Type Colorectal Cancer Vary by Regimen and Line of Therapy. Issue 3 (9th November 2022) - Parseghian, Christine M.; Sun, Ryan; Woods, Melanie; Napolitano, Stefania; Lee, Hey Min; Alshenaifi, Jumanah; Willis, Jason; Nunez, Shakayla; Raghav, Kanwal P.; Morris, Van K.; Shen, John P.; Eluri, Madhulika; et al.
Abstract : PURPOSE: Acquired resistance to anti–epidermal growth factor receptor (EGFR) inhibitor (EGFRi) therapy in colorectal cancer (CRC) has previously been explained by the model of acquiring new mutations in KRAS/NRAS/EGFR, among other MAPK-pathway members. However, this was primarily on the basis of single-agent EGFRi trials and little is known about the resistance mechanisms of EGFRi combined with effective cytotoxic chemotherapy in previously untreated patients. METHODS: We analyzed paired plasma samples from patients with RAS/BRAF/EGFR wild-type metastatic CRC enrolled in three large randomized trials evaluating EGFRi in the first line in combination with chemotherapy and as a single agent in third line. The mutational signature of the alterations acquired with therapy was evaluated. CRC cell lines with resistance to cetuximab, infusional fluorouracil, leucovorin, and oxaliplatin, and SN38 were developed, and transcriptional changes profiled. RESULTS: Patients whose tumors were treated with and responded to EGFRi alone were more likely to develop acquired mutations (46%) compared with those treated in combination with cytotoxic chemotherapy (9%). Furthermore, contrary to the generally accepted hypothesis of the clonal evolution of acquired resistance, we demonstrate that baseline resistant subclonal mutations rarely expanded to become clonal at progression, and most remained subclonal or disappeared. Consistent with this clinical finding, preclinical models with acquired resistance to either cetuximab or chemotherapy were cross-resistant to the alternate agents, with transcriptomic profiles consistent with epithelial-to-mesenchymal transition. By contrast, commonly acquired resistance alterations in the MAPK pathway do not affect sensitivity to cytotoxic chemotherapy. CONCLUSION: These findings support a model of resistance whereby transcriptomic mechanisms of resistance predominate in the presence of active cytotoxic chemotherapy combined with EGFRi, with a greater predominance of acquired MAPK mutations after single-agent EGFRi. The proposed model has implications for prospective studies evaluating EGFRi rechallenge strategies guided by acquired MAPK mutations, and highlights the need to address transcriptional mechanisms of resistance.